Kebebasan Belajar, Pembelajaran Konstruktif, dan Kemandirian Belajar dalam Mengembangkan Keterampilan Pemecahan Masalah: Studi Kualitatif Warga Belajar Pendidikan Kesetaraan - Savira Puspitasari; Muhammad Ilham Akbar (Edukhasi: Jurnal Inovasi Pendidikan, 2026)
Equivalency education programs play a crucial role in expanding access to education and supporting human development among adult learners in non-formal settings, particularly within the context of the Global South. This qualitative study explores how learning freedom, constructivist learning, and self-directed learning contribute to the development of problem-solving skills among adult learners in equivalency education programs in Greater Malang, Indonesia, with self-control examined as a mediating learning process. Using a qualitative case study approach, data were collected through in-depth interviews, participant observation, and document analysis involving adult learners, tutors, and program managers in selected Community Learning Centers. The findings indicate that learning freedom enhances learners’ motivation and relevance by enabling them to align learning activities with real-life needs. Constructivist learning practices facilitate active meaning-making through dialogue, reflection, and collaborative problem-solving, while self-directed learning strengthens learners’ responsibility and persistence within flexible learning environments. Self-control emerges as a central regulatory process that enables learners to manage emotions, sustain engagement, and make reflective decisions during problem-solving activities. This study contributes to the literature on educational development by demonstrating how learner-centered pedagogy and internal regulatory processes interact to support problem-solving skills in non-formal equivalency education. The findings offer implications for the design of equivalency education programs aimed at fostering learner autonomy, lifelong learning, and adaptability in the workforce.